A Chirality‐Returning Sequence for the Synthesis of an Unnatural Isomer of Hirsutellone B. Issue 5 (11th April 2017) - Sugata, Hayato; Kato, Ryo; Tsubogo, Tetsu; Uchiro, Hiromi
Abstract: Herein, we have achieved the synthesis of an unnatural isomer of hirsutellone B. Previously, we reported the total synthesis of the antituberculosis agent hirsutellone B. The key step in that synthetic strategy involved the direct construction of a highly strained 13‐membered macrocycle by utilizing an intramolecular Ullmann reaction. In this work, we studied the effect of the configuration at the C19 position on the macrocyclization of the 13‐membered ring. The central chirality at the C19 position of the cyclization precursor was specifically transferred to give the planar chirality of the enol ether moiety of the 13‐membered macrocycle, and the planar chirality was then transferred back to the central chirality at the C19 position of the final product. This chirality‐returning sequence enabled the stereoselective construction of the γ‐hydroxylactam of the 13‐membered macrocycle of the unnatural isomer of hirsutellone B. Abstract : Transfer at the Station : The total synthesis of an unnatural isomer of hirsutellone B was achieved by using an intramolecular Ullmann reaction to give a 13‐membered macrocycle. The central chirality at the C19 position of the cyclization precursor was transferred to the planar chirality of the enol ether moiety of the macrocycle. The planar chirality was then transferred back to the central chirality at the C19 position of the final product.